Exploring perceived transportation disadvantages: Distribution, disparities, and associations with the built environment. (November 2022) - Chen, Yuche; Wang, Sicheng; Wu, Xuanke
Abstract: We explore three perception-based transportation disadvantages: high costs or efforts, limited physical abilities, and opportunity inaccessibility. We use online panel data to synthesize perceived disadvantages for the population by census tract in South Carolina through iterative proportional updating. Hotspot analysis indicates that the three disadvantages lack statistically significant spatial relationships. We associate perception-based disadvantages with the built environment and three underrepresented communities (i.e., minority, poverty, and aging population). Findings illustrate evident social disparities in perceived transportation disadvantages. Greater residential density is associated with less physical disability and less opportunity inaccessibility. Multimodal network density has a negative association with cost or effort disadvantages. The ratio of transportation costs to household income is positively associated with physical disabilities. Minority tracts perceive more physical and accessibility disadvantages. The results provide implications for policies aiming to mitigate transportation disadvantages for underrepresented populations and neighborhoods.